A minority at the bar: Revisiting the Coptic Christian (in-)visibility. (September 2019) - Ibrahim, Mina
How do Coptic Christians make sense of a predominantly negated practice such as drinking and selling alcohol? What do they do when they are forced or voluntarily desire to join alcoholic spaces that are refused by ruling religious and social forces? In this article, I build on the unorthodoxy of beer and liquor as per the hegemonic Coptic Orthodox Church tradition of khidma in Egypt by pointing out to completely overlooked interactions that Coptic Christians have at alcoholic spaces. I argue that experiences of Coptic Christians at a bar complicate how and where Copts strive for a 'visibility' (i.e. recognition) in a country of a Muslim majority. Especially with the brutal crackdown on the post-2011 street activism following the 2013 coup, predominantly negated venues of entertainment and fun give us hints to important meanings of agency in the lives of members of the largest Christian minority in the Middle East.